Kunst Heute in Frankreich. - Becker, Wolfgang (Aachen : Neue Galerie - Sammlung Ludwig Aachen, 1987)
Alberola, Jean-Michel ; Autard, Georges ; Bartolani, Judith ; Ben ; Bioulès, Vincent ; Blais, Jean-Charles ; Boisrond, François ; Boltanski, Christian ; Cane, Louis ; Clément, Alain ; Combas, Robert ; Delprat, Hélène ; Dubuffet, Jean ; Errò ; Filliou, Robert ; Gac, Jean Le ; Garouste, Gérard ; Gasiorowski, Gérard ; Gauthier, Dominique ; Hantaï, Simon ; Hucleux, Jean-Olivier ; Klasen, Peter ; Laget, Denis ; Langlois, Jean-Yves ; Mahdavi, Rafael ; Monory, Jacques ; Nivollet, Pierre ; Pêcheur, Anne-Marie ; Poirier, Anne & Patrick ; Raysse, Martial ; Rosa, Hervé Di ; Rühle, Rütjer ; Solomoukha, Anton ; Tremblay, Daniel ; Viallat, Claude ; Voss, Jan
biog., ind. tent., gr. tent., bibliog. [1 p.] per kunstenaar
Kunst Heute in Frankreich, Neue Galerie - Sammlung Ludwig, Aachen, 1987
Duits
boek